Are Calanus spp. shifting poleward in the North Atlantic? A habitat modelling approach - Chust, Guillem; Castellani, Claudia; Licandro, Priscilla; Ibaibarriaga, Leire; Sagarminaga, Yolanda; Irigoien, Xabier (ICES Journal of Marine Science, 2014)
In the last decade, the analysis based on Continuous Plankton Recorder survey in the eastern North Atlantic Ocean detected one of the most striking examples of marine poleward migration related to sea warming. The main objective of this study is to verify the poleward shift of zooplankton species (Calanus finmarchicus, C. glacialis, C. helgolandicus, C. hyperboreus) for which distributional changes have been recorded in the North Atlantic Ocean and to assess how much of this shift was triggered by sea warming, using Generalized Additive Models. To this end, the population gravity centre of observed data was compared with that of a series of simulation experiments: (i) a model using only climate factors (i. e. niche-based model) to simulate species habitat suitability, (ii) a model using only temporal and spatial terms to reconstruct the population distribution, and (iii) a model using both factors combined, using a subset of observations as independent dataset for validation. Our findings show that only C. finmarchicus had a consistent poleward shift, triggered by sea warming, estimated in 8.1 km per decade in the North Atlantic (16.5 per decade for the northeast), which is substantially lower than previous works at the assemblage level and restricted to the Northeast Atlantic. On the contrary, C. helgolandicus is expanding in all directions, although its northern distribution limit in the North Sea has shifted northward. Calanus glacialis and C. hyperboreus, which have the geographic centres of populations mainly in the NW Atlantic, showed a slight southward shift, probably responding to cool water penetrating southward in the Labrador Current. Our approach, supported by high model accuracy, shows its power in detecting species latitudinal shifts and identifying its causes, since the trend of occurrence observed data is influenced by the sampling frequency, which has progressively concentrated to lower latitudes with time.